Determinants for disease progression in aids patients receiving treatment in the University Of Malaya Medical Centre / Rahayu Lubis - Rahayu Lubis, Abdullah (2013)
Objectives: To determine predictors of disease progression in HIV-infected patients receiving treatment at the University of Malaya Medical Centre (UMMC). Methods: HIV-infected patients aged 20 years and above on treatment in the UMMC were followed up with a bidirectional cohort study starting in 2007. Patient records were investigated retrospectively to 1986 and prospectively until 2009. Kaplan Meier and Cox regression analysis were performed using SPSS. Results: A total of 1314 patients, 73.3 per cent were aged 20-39 years, 81.8 per cent male, 61.2 per cent Chinese, 45.2 per cent single, 73.5 per cent had only primary or secondary education, 43.2 per cent worked as professionals or non-manual workers, 42.5 per cent had a monthly income of RM 1000-3000. The majority had baseline CD4 less than 200 cells/μL (62.9 per cent), viral load more than 100,000 copies/ml (51.1 per cent), hemoglobin more than 12 g/dl (62.5 per cent) and normal liver function test (55.2 per cent), were infected via the heterosexual route (65.8 per cent) and were in WHO clinical stage 4 (54.2 per cent). Most initiated HAART with 2 NRTI+ EFV (57.9 per cent), did not need second line HAART (88.5 per cent), and managed to achieve viral load less than 50 copies/ml (61.5 per cent). The median time to death in all AIDS patients was 65.7 months, and 15.0 months in AIDS patients who did not receive anti-retroviral therapy. The median time to achieve viral load less than 50 copies/ml was 5.1 months. At the end of the study, 63.6 per cent of patients survived. The predictors of death in all AIDS patients were unemployment (HR 1.59; 95% CI 1.26, 2.02), manual employment (HR 1.47; 95% CI 1.15, 1.87), those who have three or more opportunistic infections (HR 1.90; 95% CI 1.39, 2.58) and those who did not receive anti-retroviral ii therapy (HR 2.89; 95% CI 2.37, 3.47). The predictors of death in AIDS patients on HAART were unemployment (HR 1.64; 95% CI 1.04, 2.57), CD4 which never recovered to more than 200 cells/μL (HR 4.03; 95% CI 2.21, 7.35), and inability to achieve viral load less than 50 copies/ml (HR 4.39; 95% CI 2.69, 7.16). Independent predictors of death for AIDS patients who did not receive anti-retroviral therapy were Chinese ethnicity (HR 1.57; 95% CI 1.15, 2.15), baseline viral load more than 100,000 copies/ml (HR 1.35; 95% CI 1.02, 1.79) and being in WHO clinical stage 4 (HR 2.25; 95% CI 1.65, 3.06). The predictors to achieve viral load less than 50 copies/ml were starting HAART with 2NRTI+EFV (HR 1.56; 95% CI 1.10, 2.20) and not needing a second line of HAART (HR 2.59; 95% CI 1.59, 4.21) and infection via injecting drug use (HR 0.54; 95% CI 0.35, 0.80) Conclusion: Every effort needs be made to ensure all HIV-infected patients in Malaysia are able to achieve a CD4 more than 200 cells/μL, viral load less than 50 copies/ml, and have access to triple drug anti-retroviral therapy as these are significant modifiable predictors of death in Malaysian HIV patients.